2017
DOI: 10.1016/j.apenergy.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Parameter sensitivity analysis of duplex Stirling coolers

Abstract: Duplex Stirling coolers are external heat-driven regenerative machines that obtain cooling power with high efficiency and reliability. Although the technology is promising, little progress has been reported since they were invented. This paper examines the influence of system parameters on the cooling performance of a duplex Stirling cooler. The study showed that the system was sensitive to a number of parameters, as slight changes in these parameters resulted in the cooling performance deviating significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…To enhance the adaptability of DFPSC to the change of operating conditions, a motor can be used to drive the harmonic oscillator to make it as an active adjustment, which has been verified and reported by Hu et al [35] of our laboratory. In contrast, the THDPTC has no moving parts, which uses a tube to couple the engine and the cryocooler.…”
Section: Sensitivity To Operating Conditionssupporting
confidence: 62%
“…To enhance the adaptability of DFPSC to the change of operating conditions, a motor can be used to drive the harmonic oscillator to make it as an active adjustment, which has been verified and reported by Hu et al [35] of our laboratory. In contrast, the THDPTC has no moving parts, which uses a tube to couple the engine and the cryocooler.…”
Section: Sensitivity To Operating Conditionssupporting
confidence: 62%
“…is to adjust the external electric resistance to keep the displacement of the piston constant at the allowable value [46]. In a practical system, the waste heat and LNG temperatures may fluctuate.…”
Section: Parameter Sensitivity Controlmentioning
confidence: 99%
“…The study identified the COP>1 envelope of each working pair. Hu, et al [26] attributed the difficulty in having a practical working duplex Stirling heat pump to the deviation of real machines from design. The paper demonstrated how slight variations in working conditions such as temperature had a large effect of the performance of the heat pump.…”
Section: Duplex-stirling Heat Pumpsmentioning
confidence: 99%